Keamanan Maritim dan Perompakan: Studi Kasus Perompakan di Teluk Guinea - Luthfi Hanif Abdillah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Maritime piracy in the Gulf of Guinea has become a non-traditional security threat with serious implications for regional stability and global trade. Using a qualitative approach and a case study method, this study analyzes the characteristics, causes, and responses to piracy in the region. The main contributing factors include weak maritime governance, vulnerable socio-economic conditions, and transnational criminal networks. Although several initiatives such as the Yaoundé Code of Conduct and the YARIS system have been implemented, coordination challenges and limited capacity remain significant obstacles. This study emphasizes the importance of a multidimensional approach and cross-border cooperation to achieve sustainable maritime security.